2015
DOI: 10.1093/nar/gkv961
|View full text |Cite
|
Sign up to set email alerts
|

DnaC traps DnaB as an open ring and remodels the domain that binds primase

Abstract: Helicase loading at a DNA replication origin often requires the dynamic interactions between the DNA helicase and an accessory protein. In E. coli, the DNA helicase is DnaB and DnaC is its loading partner. We used the method of hydrogen/deuterium exchange mass spectrometry to address the importance of DnaB–DnaC complex formation as a prerequisite for helicase loading. Our results show that the DnaB ring opens and closes, and that specific amino acids near the N-terminus of DnaC interact with a site in DnaB's C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 67 publications
1
50
0
Order By: Relevance
“…The Mutant DnaCs Are Able to Interact with DnaB-Studies indicate that two sites near the N terminus of DnaC interact with DnaB in the DnaB-DnaC complex (10,28). Hence, we expected that the substitutions would not cause impaired binding to DnaB because they do not reside in these sites.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Mutant DnaCs Are Able to Interact with DnaB-Studies indicate that two sites near the N terminus of DnaC interact with DnaB in the DnaB-DnaC complex (10,28). Hence, we expected that the substitutions would not cause impaired binding to DnaB because they do not reside in these sites.…”
Section: Resultsmentioning
confidence: 99%
“…11 and 17. The residues shaded in gray represent segments that bind to DnaB (28). Those shaded in blue correspond to the initiator specific motif (ISM; residues 136 -162) (12).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic and biochemical studies demonstrated that amino acid substitutions within residues 8–11 and 31–44 of DnaC abrogate its interaction with DnaB and the function of DnaC in replication initiation [140]. In hydrogen-deuterium exchange experiments, which measures protein dynamics by the relative ability of amide hydrogens in a protein to exchange with deuterium in a buffer made with heavy water, peptides corresponding to these segments of DnaC were found to become occluded when DnaC is complexed to DnaB [141]. Together, these results indicate that these regions of DnaC interact directly with DnaB.…”
Section: Mechanism Of Initiationmentioning
confidence: 99%
“…Other evidence showed that mutant DnaBs bearing I297A, L304A, or E435A substitutions are defective in complementing a temperature-sensitive dnaB mutant at nonpermissive temperature [141]. To substantiate that the E435A substitution interferes with DnaB function, biochemical experiments were performed, which showed that this protein is inactive in DNA replication of an oriC -containing plasmid.…”
Section: Mechanism Of Initiationmentioning
confidence: 99%